Special nuclear layer contacts between starburst amacrine cells in the mouse retina - Mu, Shang; Turner, Nicholas L.; Silversmith, William M.; Jordan, Chris S.; Kemnitz, Nico; Sorek, Marissa; David, Celia; Jones, Devon L.; Bland, Doug; Moore, Merlin; Sterling, Amy Robinson; Seung, H. Sebastian (Frontiers in Ophthalmology, 2023)
The starburst amacrine cells are a prominent neuron type in the mammalian retina, well studied for their role in direction-selective information processing. One specific property of these cells is that their dendrites tightly stratify at specific depths within the inner plexiform layer (IPL), which together with their unique expression of choline acetyltransferase (ChAT) resulted in them becoming the most common depth landmark for studying other retinal neurons in IPL. This stratifying property makes it unexpected that they could have dendrites routinely reaching into the nuclear layer or that they could have somatic contact specializations, which are just what we have found with this report. Specifically, an electron microscopic image volume of sufficient size from a mouse retina provided us with the opportunity to anatomically observe both microscopic details and collective patterns, and our detailed cell reconstructions revealed interesting cell-cell contacts between starburst amacrine neurons. The contact characteristics differ between the respective On and Off starburst amacrine subpopulations, but both occur within the soma layers as opposed to their regular laminae of contact within the inner plexiform layer.